Factors influencing the adoption of digital technology among working millennials - Hefvihervina Rohayu, Hariyanto (2022)
Industrial revolution 4.0 (IR 4.0), has gained high attention in Malaysia and become a national agenda. IR 4.0 which emphasize on the digital technology, helps business sector to increase customer satisfaction, enhance creativity and innovation, create high-level performance and sustain business competitiveness. Despite its growing importance, there are individuals who are still sceptical to adopt technology. Given that millennials are the largest generational cohort in the current employment, understanding the factors that may contribute to technology adoption among this generational cohort is crucial. Thus, this study aims to examine a relationship between organization support, social support and individual innovativeness; and technology adoption. Convenient sampling method was used. Three hundred and nine working millennials in Kuala Lumpur have participated in this study. Multiple Regression Analysis was used to examine the patterns of relationship among the variables and to empirically test the hypothesis. The result shows that only social support and individual innovative has a positive significant relationship with digital technology adoption. Whereas, organization support has shown insignificant relationship with digital technology adoption. Based on the findings of the study, it indicates that managers should consider social support and individual innovativeness if they were to enhancing the adoption of digital technology among working millennials in Kuala Lumpur.